Role of Family Support and Its Significance in Rehabilitative Care among Stroke Patients and Depression - Fadhilah, Adinda; Pahria, Tuti; Nursiswati, Nursiswati; Acob, Joel Rey (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Stroke incidence increases with age, and the combination of a growing population and aging demographics is expected to lead to a significant rise in global mortality and disability in the future. Stroke survivors experience substantial health, emotional, social, and economic impacts, which are felt not only by individuals but also by families and communities. This study aimed to identify the relationship between depression level and stroke severity with family support in post-stroke patients at Sumedang Regency Hospital. This study used quantitative methods with a cross-sectional design. A total of 123 post-stroke patients participated in this study. Data were collected using the Beck Depression Inventory-II (BDI-II) questionnaire, National Institutes of Health Stroke Scale (NIHSS), and Perceived Social Support-Family (PSS-Fa), and analyzed using the Chi-Square test. Statistical tests showed a significant relationship between stroke severity and family support in post-stroke patients with a p value of 0.017 (p value <0.05), as well as between depression level and family support in post-stroke patients with a p value of 0.001 (p value <0.05). There is a significant relationship between stroke severity and depression level with family support in post-stroke patients. To improve health outcomes, it is important for healthcare providers to develop and implement strategies that strengthen family involvement in post-stroke patients care.